1988
DOI: 10.1021/j100313a020
|View full text |Cite
|
Sign up to set email alerts
|

Electronic relaxation of xenon chloride (Xe2+Cl-) in solid and liquid xenon

Abstract: lation suggesting that the stable conformation of the radical is planar,9 and thus it might be possible to assert that the circumstances of the canal complex make the nonplanar structure stable. If the above assertion is true, it follows that the most stable conformation (S) is pyramidal and the next stable one (U) is planar as in the MINDO calculation. These two structures cannot exist at the same time unless unreasonable structures are assumed.However, if a pyramidal conformation is the most stable at the eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The latter consideration makes these systems ideal for the study of solvation dynamics, in particular since these exciplexes are long lived in the liquid phase--in dilute solutions the relaxation is dominated by radiation; in concentrated solutions the relaxation is due to diffusion controlled encounters of the exciplex with the parent molecular halogen. 15 It is important to point out that with the exception of XeEF, all of these emissions are stable with respect to duration of excitation. In contrast with the low temperature matrices, in the liquids the halogen atoms are free to recombine between exaltation pulses.…”
Section: Liouid Phase Exciplexes and Photo-induced Harpooningmentioning
confidence: 98%
“…The latter consideration makes these systems ideal for the study of solvation dynamics, in particular since these exciplexes are long lived in the liquid phase--in dilute solutions the relaxation is dominated by radiation; in concentrated solutions the relaxation is due to diffusion controlled encounters of the exciplex with the parent molecular halogen. 15 It is important to point out that with the exception of XeEF, all of these emissions are stable with respect to duration of excitation. In contrast with the low temperature matrices, in the liquids the halogen atoms are free to recombine between exaltation pulses.…”
Section: Liouid Phase Exciplexes and Photo-induced Harpooningmentioning
confidence: 98%
“…15 and 16͒ and Cl 2 ͑Refs. 17-19͒, together with experimental studies of these systems [19][20][21][22][23][24][25][26][27] have demonstrated both caging and mobility of photoproducts. The dynamics of halogens in rare gas solids at high kinetic energies are sensitive to the nonadiabatic processes involving curve crossings between valence, Rydberg, and charge transfer states, and the interaction of the matrix host with these states.…”
Section: Introductionmentioning
confidence: 99%
“…This discovery clearly delineates the underlying mechanism for the process as one in which the synergistic excitation of the two absorbing species results from molecular proximity rather than any collisional effect. The reaction mechanism (1.1) has been further corroborated by Apkarian and co-workers, who have also extended the study to charge transfer reactions in solid and liquid xenon (Fajardo and Apkarian 1986Wiedeman et al 1987Wiedeman et al , 1988. It has additionally been shown to be the predominant reaction route in the case of Xe:Cl, van der Waals complexes generated in seeded molecular beams (Boivineau et al 1986a, b).…”
Section: Introductionmentioning
confidence: 62%